Protective effect of human leukocyte antigen B27 in hepatitis C virus infection requires the presence of a genotype-specific immunodominant CD8+ T-cell epitope - Neumann-Haefelin, Christoph; Timm, Jörg; Schmidt, Julia; Kersting, Nadine; Fitzmaurice, Karen; Oniangue-Ndza, Cesar; Kemper, Michael N.; Humphreys, Isla; McKiernan, Susan; Kelleher, Dermot; Lohmann, Volker; Bowness, Paul; et al. (Hepatology, 2010)
Human leukocyte antigen B27 (HLA-B27) is associated with protection in human immunodeficiency virus (HIV) and hepatitis C virus (HCV) infection. This protective role is linked to single immunodominant HLA-B27-restricted CD8+ T-cell epitopes in both infections. In order to define the relative contribution of a specific HLA-B27-restricted epitope to the natural course of HCV infection, we compared the biological impact of the highly conserved HCV genotype 1 epitope, for which the protective role has been described, with the corresponding region in genotype 3 that differs in its sequence by three amino acid residues. The genotype 3a peptide was not recognized by CD8+ T cells specific for the genotype 1 peptide. Furthermore, patients with acute or chronic infection with HCV genotype 3a did not mount T-cell responses to this epitope region, and their autologous viral sequences showed no evidence of T-cell pressure. Finally, we found a significantly higher frequency of HLA-B27 positivity in patients with chronic HCV genotype 3a infection compared to genotype 1 infection, indicating that there is no protection by HLA-B27 in HCV genotype 3 infection. Conclusion: Our data indicate that the protective effect of HLA-B27 is limited to HCV genotype 1 infection and does not expand to other genotypes such as genotype 3a. This can most likely be explained by intergenotype sequence diversity leading to the loss of the immunodominant HLA-B27 epitope in viral strains other than genotype 1. Our results underline the central role of a single HLA-B27-restricted epitope-specific CD8+ T-cell response in mediating protection in HCV genotype 1 infection. (HEPATOLOGY 2010;51:54-62.)
Online veröffentlicht: 23 December 2009
Gesehen am 12.05.2023